Foliar application of sodium selenite affects the growth, antioxidant system, and fruit quality of strawberry - Lin, Yuanxiu; Cao, Shuaipeng; Wang, Xiao; Liu, Yin; Sun, Ziqing; Zhang, Yunting; Li, Mengyao; Wang, Yan; He, Wen; Zhang, Yong; Chen, Qing; Wang, Xiaorong; et al. (Frontiers in Plant Science, 2024)
Introduction Selenium (Se) plays a vital role in various physiological processes in plants and is regarded as an essential micronutrient for human health as well. Methods In this study, sodium selenite solution at 10, 40, 70, and 100 mg·L-1 concentrations was foliar sprayed, and the strawberry plant growth, antioxidant system, and fruit quality with an emphasis on sugar and acid content were assessed. Results The results showed that 10 mg·L-1 of sodium selenite treatment promoted plant growth, while all the treated concentrations could enhance photosynthesis, the antioxidant system in leaves, the content of Se, and ascorbic acid in fruits. More importantly, 40 mg·L-1 sodium selenite treatment significantly increased fruit weight, total soluble solid, total phenolic content, and anthocyanins, as well as improved the shape index. Furthermore, it decreased the total flavonoid and proanthocyanidin content. Particularly, sodium selenite treatment at 40 and 70 mg·L-1 largely increased the ratio of soluble sugars to titratable acid. The changes of predominant sugars and organic acids during fruit development were further investigated. The sucrose, fructose, and glucose content was upregulated by sodium selenite treatment through upregulating the activities of sucrose phosphate synthase (SPS) and acid invertase, as well as the FaSPS expression. In addition, sodium selenite treatment inhibited the activity of citrate synthase and phosphoenolpyruvate carboxylase, rather than modulating their transcript levels to reduce the citric acid content. Conclusions This work presented a potentially efficient approach to enhance plant growth and fruit quality and supplement Se in strawberry, providing insights into the mechanism of regulating sugar and acid metabolism by Se.